PURIFICATION AND CRYSTALLIZATION OF MICROBIAL XYLITOL FROM HYDROLYSATE OF LIGNOCELLULOSE USING MEMBRANE TECHNOLOGY - Qoharisma Salam, Wildan
Xylitol is a sugar alcohol that could be used as a sweetener in food products. lts sweetness level is comparable to sucrose but has a much lower calorie and glycemic index. Xylitol could be produced through a biotechnological process by fermenting a xylose solution or hemicellulose hydrolyzate. The xylitol fermentation solution produced through the biotechnology process still has impurities that need to be separated. ln addition, xylitol is commercialized in the form of crystalline powder. Therefore, it is necessary to conduct downstream processing of the xylitol fermentation solution.